2011
DOI: 10.1002/rra.1578
|View full text |Cite
|
Sign up to set email alerts
|

Fish Assemblages at Engineered and Natural Channel Structures in the Lower Missouri River: Implications for Modified Dike Structures

Abstract: Large rivers throughout the world have been modified by using dike structures to divert water flows to deepwater habitats to maintain navigation channels. These modifications have been implicated in the decline in habitat diversity and native fishes. However, dike structures have been modified in the Missouri River USA to increase habitat diversity to aid in the recovery of native fishes. We compared species occupancy and fish community composition at natural sandbars and at notched and un‐notched rock dikes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
(71 reference statements)
1
17
0
Order By: Relevance
“…() and Schloesser et al . () did not detect large differences to the fish community as a whole among dike types. Differences between L‐dikes and un‐notched dikes were apparent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Schloesser et al . () did not detect large differences to the fish community as a whole among dike types. Differences between L‐dikes and un‐notched dikes were apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Schloesser et al . () studied fish use of notched dikes, un‐notched dikes and natural channel sand bars in the lower Missouri River and found that for 81% of the fish species examined, notching did not affect occupancy or abundance. Battle et al .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of SSCV areas in other large river systems has prompted their artificial development for the benefit of native fishes. For example, a variety of approaches (e.g., notching dikes) have been used to create new SSCV habitats in the Missouri River to provide refuge for small-bodied and juvenile native fishes (Papanicolaou, Elhakeem, Dermisis, & Young, 2011;Ridenour, Starostka, Doyle, & Hill, 2009;Schloesser et al, 2012). Engineered SSCV habitats in the Mississippi River, United States, and Huntspill River, United Kingdom, have resulted in increased abundance and diversity of Age-0 fishes when compared with main channel areas (Barko, Herzog, Rabik, & Scheibe, 2004: Langler & Smith, 2001.…”
Section: Our Analyses Indicated That Occurrence and Abundance Of Severalmentioning
confidence: 99%
“…With an increasing focus on species conservation (e.g., Schloesser et al, 2012;Theiling et al, 1999), lotic systems have become a target for restoration and rehabilitation projects in an attempt to mitigate the effects of anthropogenic disturbance (Bernhardt et al, 2005;Gore & Shields, 1995;Lake, Bond, & Reich, 2007). Placement of large woody habitat features and other engineered structures (e.g., dikes and riprapped shoreline) in rivers and streams has become one of the most common techniques used to improve fish habitat (Madejczyk, Mundahl, & Lehtinen, 1998;Roni, Beechie, Pess, & Hanson, 2015;Schloesser et al, 2012). Another common rehabilitation technique is the creation or reconnection of off-channel habitat units that provide areas of shallow water and reduced current velocity (e.g., side channels and backwaters; Roni et al, 2002).…”
mentioning
confidence: 99%
“…The fishes of these modified systems have been extensively studied (Sparks and Starrett 1975;Madejczyk et al 1998; Barko et al 2004aBarko et al , 2004bOscaz et al 2005;Schloesser et al 2011;Alexander et al 2012) because of their high ecological, commercial, and recreational value. Other vertebrate species, such as turtles, are ecologically important as nutrient vectors in river systems (Dreslik et al 2005;Sterrett et al 2015) but have received less attention, even though freshwater turtles face many unique challenges that have important implications for their conservation (Bodie 2001).…”
mentioning
confidence: 99%